A Push–Pull PdII Complex with a Ternary Pd–P–C+ Accepting End and a Key N‐Heterocyclic Carbene–Imidazoliophosphine Ligand. Issue 3 (11th December 2015) - Dubrulle, Laurent; Poidevin, Corentin; Maaliki, Carine; Canac, Yves; Lepetit, Christine; Duhayon, Carine; Chauvin, Remi
Abstract: Neutral and cationic PdCl2 complexes based on the neutral frame of a cis ‐chelating N‐heterocyclic carbene (NHC)–imidazolophosphine ligand involving an o ‐phenylene bridge have been devised for comparison of their relative push–pull character. Both target complexes, which are globally isosteric in the Pd coordination sphere, have been prepared in 58–68 % yield by direct coordination of the corresponding cis ‐chelating NHC‐imidazol(i)ophosphine "free ligand", or by extrusion of a Ph2 P + phosphenium moiety from (imidazoliophosphine)Pd II complex precursors. The cationic complex has also been obtained in 64 % yield by selective N ‐methylation of the neutral counterpart. The charge transfer from the NHC donating end (LD ) to the imidazol(i)ophosphine accepting end (LA ) has been investigated by electronic spectroscopy and by calculations of the first excited states at the time‐dependent (TD)‐DFT level. Although all the excitations involving the LD and LA ends of the neutral complex converge to the Pd center, the excited states |S7 > (305 nm) and |S8 > (303 nm) of the cationic complex exhibit a net LD [M]LA charge‐tranfer (CT) character, which is clearly visualized by particle–hole density analysis. The push–pull complex involving a Pd–P–C + π‐accepting end is regarded as a "ternary" counterpart of "binary" phosphine–borane complexes involving two‐center Pd–B σ‐accepting ends. Abstract : N ‐Methylation of a neutral N‐heterocyclic carbene (NHC)–imidazolophosphine ligand chelating a PdCl2 fragment affords a globally isosteric cationic push–pull complex exhibiting low‐energy charge‐transfer (CT) excited states of the LD [M]LA CT type.